Novel Insights into Surface Energies and Enhanced Gas-Sensing Capabilities of ZnGa2O4(111) via Ab Initio Studies - Cheng-Lung Yu; Yan-Cheng Lin; Sheng-Yuan Jhang; Jine-Du Fu; Yi-Chen Chen; Po-Liang Liu (Sensors)
This study investigates the surface energies and work function changes in ZnGa2O4(111) surfaces with different atomic terminations using ab initio density functional theory. It explores the interactions of gas molecules such as NO, NO2, and CH3COCH3 with Ga-terminated, O-terminated, and Ga-Zn-O-terminated surfaces. This study reveals previously unreported insights into how O-terminated surfaces exhibit enhanced reactivity with NO, resulting in significant work function changes of +6.42 eV. In contrast, Ga-terminated surfaces demonstrate novel interactions with oxidizing gases, particularly NO2, with a notable reduction in work function change of −1.63 eV, offering potential gas sensor technology advancements. Particularly notable is the Ga-Zn-O-terminated surface, which presents mixed characteristics influenced by the interplay of oxygen and metallic elements (gallium and zinc), leading to substantial work function changes of +4.97 eV for NO and +1.82 eV for NO2, thereby significantly enhancing sensitivity. This study unveils the previously unexplored roles of Ga-Zn-O-terminated ZnGa2O4 surfaces in optimizing semiconductor-based gas sensors, offering both oxidative and reductive potentials and making them versatile for diverse applications.